THE PATTERN OF APPLYING RELIGIOUS MODERATION IN THE WORLD OF MADRASAH EDUCATION THROUGH ARABIC LANGUAGE TEXTBOOKS - Muhammad Nanang Qosim (IAIN Surakarta, 2021)
The study of how to apply religious moderation to textbooks is a linguistic discourse as a unit of language embodied in written form with a complete message. The form described in this study is represented by words and phrases related to the way of applying religious moderation. This study aims to reveal how religious moderation is applied in madrasah textbooks. The research method in this study uses a qualitative method with descriptive analysis with Arabic book data sources Mts (Madarasa Tsanawiyah) published by the Ministry of Religion of the Republic of Indonesia in 2019. The results of this research are the values of moderation in the Arabic books of Mts which are the messages to be conveyed to students and the patterns of the application of religious moderation in books, namely the macrostructure and the microstructure. The pattern of forming the meaning of religious moderation in textbooks is presented in text form.